TECHNOLOGY-ENHANCED LEARNING BEYOND ARTIFICIAL INTELLIGENCE - Alimnazarava , Nafisa; Joʻrabekova , Robiya; O'razova , Marjona; Safarova , Asal (Zamonaviy ilmiy yondashuvlar va texnologik taraqqiyotning ustuvor yo‘nalishlari, 2026)
This article analyses the effectiveness of non‑AI digital learning tools – virtual and augmented reality, mobile learning, game technologies, learning analytics, blended learning, and social media – in educational settings. Based on systematic reviews and meta‑analyses published between 2015 and 2025. Results show that game technologies increase activity and motivation; augmented reality is suitable for novice learners, while virtual reality may impose cognitive load. Learning analytics can identify at‑risk students but remains weak in providing actionable classroom advice. Mobile learning increases flexibility, though most studies are short‑term. Blended learning produces positive outcomes in most countries. Social media can increase participation by up to 40 percent, but privacy risks remain. Conclusion: digital tools can enhance learning, but their use must align with pedagogical goals and context.